Folates retention in brassica vegetables consumed in Brazil after different cooking methods - Della Lucia, Ceres M; Rodrigues Da Silva Mota, Elizangela; Aguiar Montini, Tatiana; R. Ribeiro, Sônia M.; P. Chaves, José Benício; Pinheiro-Sant’Ana, Helena M. (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
The present study aimed to determine the effects of different traditional cooking methods on folate (tetrahydrofolate - THF, 5-methyltetrahydrofolate - 5- MTHF and 5-formyltetrahydrofolate - 5-FTHF) retention in leafy vegetables. The analysis of folates was carried out by high performance liquid chromatography (HPLC), with detection by fluorescence, using gradient elution, mobile phase of acetonitrile and phosphate buffer solution. The retention of isomers in vegetables after cooking ranged from 17.0 % to 87.2 % for THF, 53.4 – 94.1% for 5-MTHF and 39.0 – 107.9% for 5-FTHF. The retention of folates depended on the food matrix, the kind of isomer, and the cooking methods used. It is recommended that one should have more control over the choices for methods and time of cooking and the amount of water used at home and at foodservice as well. El presente estudio tuvo como objetivo determinar los efectos de los diferentes métodos de cocción tradicionales sobre la retención de folatos (tetrahidrofolato - THF, 5-metiltetrahidrofolato - 5- MTHF y 5-formiltetrahidrofolato - 5 FTHF) en hortalizas. El análisis de folatos se llevó a cabo por cromatografía líquida de alta resolución (CLAR), con detección por fluorescencia, usando elución en gradiente, fase móvil de acetonitrilo y solución tampón de fosfato. La retención de los isómeros en las hortalizas después de la cocción varió de 17,0% a 87,2% para THF, 53,4 a 94,1% para 5-MTHF y de 39,0 a 107,9% para 5- FTHF. La retención de folatos dependió de la matriz del alimento, el tipo de isómero, y los métodos de cocción utilizados. Se recomienda que uno debe tener más control sobre las opciones de métodos y tiempo de cocción y la cantidad de agua utilizada en el hogar y también en los servicio de alimentación.